Granulomatous-lymphocytic interstitial lung disease mimicking Sarcoidosis. : GLILD case series - Perlman, David; Sudheendra, Muthya Tejasvini; Racilla, Emilian; Allen, Tadashi; Bhargava, Maneesh (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2021)
Common variable immunodeficiency (CVID) is the most common primary immunodeficiency characterized by hypogammaglobulinemia and inadequate antibody response to immunizations. The impaired antibody response occurs due to the failure of B cells to differentiate into plasma cells resulting in low immunoglobulins levels and increased frequency of infections. Granulomatous and Lymphocytic Interstitial Lung Disease (GLILD) is a non-infectious complication of CVID that is seen in 10-30% of cases. GLILD is a multisystem disease involving the lungs, lymph node, liver, spleen and gastrointestinal tract that mimics sarcoidosis. This report describes a series of cases who presented with dyspnea, recurrent respiratory infections or autoimmunity and on workup revealed features suggestive of GLILD. The literature on the clinical features, the histological findings, and the diagnostic criteria are limited. A diagnosis of GLILD is established in cases of CVID when there is evidence of lymphoproliferation, cytopenia, autoimmune processes and a lung biopsy demonstrating lymphocytic interstitial pneumonia, follicular bronchiolitis, lymphoid hyperplasia, and non-necrotizing granulomas. We review the treatment strategies, including replacement of immunoglobulin and agents targeting B and T lymphocytes. Systematic characterization of GLILD cases and long term follow up studies are needed for filling the knowledge gaps in GLILD.